Informing future quarantine practices through the experiences of COVID‐19 quarantine facility staff - Angela Sheedy; Dianne Stephens; Lisa Vermeulen (Wiley, 2024)
Abstract Background The COVID‐19 pandemic necessitated the rapid development of quarantine sites, prompting the need for new staff models and scopes of practice. This project surveyed health and non‐health staff at a large outdoor quarantine facility in regional Australia to gather insights for future quarantine facility guidelines based on their experiences and perceptions. Methods This translational research project implemented a mixed‐methods approach to analyse staff perceptions of working at a quarantine facility to inform the development of a policy and practice guide. An anonymous online survey utilising purposive sampling was distributed to 410 multidisciplinary survey participants over an 8‐week period. Survey questions focussed on site processes, challenges and recommendations for future implementation of quarantine services. Qualitative data was thematically analysed with the aid of Leximancer, and a descriptive statistical method was used for quantitative data analysis. Results There were 92 survey respondents from health and non‐health roles; of these, 85% indicated they would work at the quarantine facility again, and 90% agreed residents were well cared for. There was a lack of anxiety of acquiring COVID‐19, with 95% feeling safe from COVID‐19 transmission onsite. Challenges staff identified highlighted future investment areas, including leadership communication models, information technology (IT) management systems specific for quarantine services and site processes to better accommodate weather elements. Conclusion Overall, staff validated the primary health model of quarantine care with key challenges highlighting the importance of leadership and investment in communication and IT. The results were aligned with site functions and operations and will inform the development of a pandemic quarantine facility guide.